Comparision of the Color Properties of Compounds Ln2Ce2O7 and Ln2CeZrO7 - Hablovičová Blanka; Šulcová Petra (My University, 2015)
Pyrochlore type pigments with general formulas Ln2Ce2O7 and Ln2CeZrO7 (Ln = Nd, Sm, Gd, Dy, Er, Yb, Y) prepared by solid-state reaction were investigated. Color properties in organic matrix and ceramic glazes, particle size distribution and phase composition were evaluated.
Porovnání barevných vlastností sloučenin Ln2Ce2O7 a Ln2CeZrO7
Keywords: Lanthanide Oxides; Pyrochlore; Inorganic Pigment; Zirconium Oxide; Oxidy lanthanoidů; pyrochlor; anorganický pigment; oxid zirkoničitý